ASSESSMENT OF THE CONTENT OF HARMFUL CHEMICALS IN THE AIR - Sharipova Sojida Ahmadjanovna (Modern American Journals, 2025)
Relevance of the study. Maintaining occupational health is an important function of the state in implementing its social policy, which determines the potential and pace of the country's economic development. Urban health issues continue to be a priority and challenging area in the field of human ecology and environmental health. A modern wastewater disposal system is a vital component of a metropolis' infrastructure, protecting the environment from pollution. However, the operation of such complex technological structures is associated with a variety of risks that can disrupt not only the normal functioning of the city but also negatively impact human health and the environment. Domestic and international literature contains publications attesting to the attention of scientists to the problem of wastewater treatment, primarily from the perspective of water body sanitary protection. However, a modern understanding of the wastewater treatment process is inextricably linked to improving working conditions and assessing the incidence of illness among service personnel.